Reflections on information and communication technologies in the public school by an autobiographic viés (Research, Society and Development, 2019)
Thinking about the scope of Information and Communication Technologies (TIC) and media in the contemporary public school is essential to make use of them in a conscious and responsible way with the possibility of generating a meaningful learning of the students through these tools. Therefore, the present work aims to reflect on the insertion of TIC and the media in the context of the public school under an autobiographical bias. These reflections emerge from the experiences of educators who act or have acted in the public teaching network as regent teachers and/or participants in programs of initiation to teaching and internships. We conclude that TIC and media can collaborate a lot with the teaching-learning process, but we also emphasize that these tools are pedagogical complements and cannot be the purpose of the teacher's work. In addition, we emphasize that in some of our contexts of action, its non-use often refers to deficient school infrastructures and lack of knowledge, lack of technological mastery and/or traditionalism of teaching practice. Therefore, we understand that TIC and the media need to be debated and their contexts of insertion in the school being observed from each school reality so that one has a clear reading of its insertions and its foundations in pedagogical practices.